GPCR antibody screen - Dahl, Leo (SciLifeLab Serve, 2026)
Visualizations of the results from a selectivity screen of >400 antibodies targeting 215 G protein-coupled receptors (GPCRs). Companion app to 'Multiplexed selectivity screening of anti-GPCR antibodies', https://doi.org/10.1126/sciadv.adf9297